Methods of sampling applied to Irish statistics - Geary, R. C. (Statistical and Social Inquiry Society of Ireland, 1925)
As the Society is aware, during the recent troubles the system of complete enumeration of agricultural statistics broke down in this country, and since then it has been necessary to rely on estimates derived from a sample of returns received through the post from a very large number of farmers distributed all over the country. It is proposed to change this system this year to a sample of districts, but before doing so it was necessary to investigate the error which the method involved, and this paper is the outcome of that investigation.
Read Friday, 27th February, 1925
Keywords: Statistical methods; Statistical sampling; Agricultural statistics; Farming analysis; 314.15